About the theory and empirical analysis of “the persistence of profit”and its applicability to Colombia (2020)
This paper looks into the application of the theory of “the persistence of profits” and how it can be used to model manufacturing industries in Colombia. By explaining where the theory of “persistence of profits” comes from, what it is, and what its determinants are brief descriptions of the theory is given. This paper proposes a model for examining persistence of profits in Colombian manufacturing industry. By analyzing the literature and the modeling in developed countries the model takes into account the characteristics of the manufacturing industry.